The Catholic Bishops of Europe and the Nazi Persecutions of Catholics and Jews - Lapomarda, Vincent A. (Lewiston : Edwin Mellen Press, 2012)
The book describes the role way some Catholic Bishops attempted to resist the Nazi extermination of the Jews and other populations during the Holocaust. It shows that many Catholic Bishops throughout Europe risked life and limb sheltering Jews and other victims. While other scholars forward different opinions on the matter, Lapomarda's analysis of Pope Pius XII uses factual evidence to show the Pope acted against the Nazis' treatment of the Jews, and facilitated massive movements against the final solution.
Description based upon print version of record.
Keywords: Catholic Church -- Europe -- Bishops -- History -- 20th century; Catholics -- Europe -- History -- 20th century; Catholics -- Nazi persecution; Jews -- Europe -- History -- 20th century; Jews -- Persecutions -- Europe; Persecution -- Europe -- History -- 20th century; World War, 1939-1945 -- Atrocities; RELIGION / Christian Church / Leadership; RELIGION / Leadership; Catholic Church -- Europe -- Bishops -- History -- 20th century; Catholics -- Nazi persecution; Jews -- Persecutions -- Europe; World War, 1939-1945 -- Atrocities; Persecution -- Europe -- History -- 20th century; Catholics -- Europe -- History -- 20th century; Jews -- Europe -- History -- 20th century; Electronic books